Effect of Coarse Aggregate and Slag Type on the Mechanical Behavior of High and Normal Weight Concrete Used at Barrage Structure : Effect of Coarse Aggregate and Slag Type on the Mechanical Behavior of High and Normal Weight Concrete Used at Barrage Structure - Muhammad Sanaullah; Sajid Rashid Ahmad; ZaheerYousaf; Zaheer Abbas; Zaeem Hassan Akhtar; Menal Zaheer; Ali Hamza (International Journal of Economic and Environmental Geology, 2017)
Present study is an effort to assess the composite effect of limestone aggregate and blast furnace slag on the mechanical characteristics of normal and high weight concrete at various structural units (barrage girders, main weir and block apron) of New Khanki Barrage Project, Punjab. Mix designs for different concrete classes falling under the domain of high and normal weight concrete were prepared after aggregate quality testing. On attaining satisfactory results of quality testing nine concrete mixes were designed (three for each class: A1, A and B) by absolute volume method (ACI- 211.1). The required compressive strength of normal and high strength was set at 6200, 5200 and 4200 Psi for the concrete types A1, A and B respectively after 28 days (ACI -318). For compressive strength assessment, a total 27 concrete cylinders were casted (9-cylinders for each mix) and were water cured. The achieved average UCS of cylinder concrete specimens at 3, 7 and 28 days are 5170, 6338 and 7320 Psi for A1 – type, 3210, 4187 and 5602 Psi for A-type and 2650, 3360 and 4408 Psi for B- type mix. It has been found that all concrete mixes for suggested classes attained target strength at age of 7-days. The coarse aggregate (Margala Hill limestone) and fine aggregates (from Lawrancepur /Qibla Bandi quarries) used in all concrete mix designs have demonstrated a sound mechanical suitability for high and normal weight concrete. Keywords: Limestone, aggregate, compressive strength, concrete mix design.